3a+1=-3.6(a-10)

Simple and best practice solution for 3a+1=-3.6(a-10) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3a+1=-3.6(a-10) equation:



3a+1=-3.6(a-10)
We move all terms to the left:
3a+1-(-3.6(a-10))=0
We calculate terms in parentheses: -(-3.6(a-10)), so:
-3.6(a-10)
We multiply parentheses
-3.6a+36
Back to the equation:
-(-3.6a+36)
We get rid of parentheses
3a+3.6a-36+1=0
We add all the numbers together, and all the variables
6.6a-35=0
We move all terms containing a to the left, all other terms to the right
6.6a=35
a=35/6.6
a=5+1/3.3

See similar equations:

| 6p–4+12p=-20+16p | | 15=13-x | | 2+2x=6x-2 | | 2.27x-0.27x+0.6=11.0 | | x2+2x+5=0 | | 6+2(3j-2)=4(1+j | | 5f-41=3f-9 | | .05X+.1X+.25x=2 | | -3n+-4n-5=0 | | 4x²+6x=0 | | 5x-15=20- | | .5X+.1X+.25x=2 | | 2y^2+3y=27 | | −2(7+2k)=3k | | -5m=100 | | -15n*18n+-4n-5=0 | | 2x^2+17x=-8 | | 3/2(9x-6)=8 | | 10-m=-30 | | X(2x-5)=(2x+5)(x-4) | | 3x-10=5(x+2)-2x | | -0.8x=64 | | 4/2x-1=3/11 | | 5(4+2x)=0 | | 8-3(-12x+2)=0 | | 8=2/3(9x-6) | | 14u-13u-1=17 | | 2.6v=7.5 | | 10x-2x-9=-45+12x | | X+2x+3x+3=21 | | 2y+6y=-8 | | 2x-35+5x=0 |

Equations solver categories